Educational Data Mining in Online Learning: Data Mining Techniques and Algorithms, Factors, Equity and Accessibility Dimensions (A Systematic Literature Review) - Imalatul Hidayah; Ririen Kusumawati (Universitas Islam Raden Rahmat, Malang, 2026)
This Systematic Literature Review (SLR) examines the application of Educational Data Mining (EDM) in online learning from 2015 to 2025 using the PRISMA approach. Thirty-two studies were analyzed to identify the data mining techniques used, the factors analyzed, and the extent to which the literature considers the equity and accessibility dimensions. The review results indicate that EDM is widely applied to predict academic performance, identify learning behavior patterns, detect at-risk students, and analyze the use of learning resources. The dominant techniques include classification, prediction, sequence analysis, process mining, and clustering. However, the equity and accessibility aspects are rarely discussed explicitly most studies only implicitly address accessibility through digital interaction behavior, while social factors related to equity, such as learning readiness, environmental support, and the digital divide, appear in only a small proportion. Furthermore, the variety of data formats and limited course coverage limit the generalizability of the findings. Overall, this study emphasizes the need for stronger integration between educational analytics and the social dimension for EDM to more effectively support equitable distribution of quality and access to online learning.